Experimental evidence of mate choice as the driving mechanism behind negative assortative mating for shell colour in a marine snail - Gefaell, Juan; Vigo, Ramón; Galindo, Juan; Rolán-Alvarez, Emilio (Biological journal of the Linnean Society, 2024)
Abstract How colour polymorphisms are maintained in natural populations constitutes a key subject of study for evolutionary ecologists. One of the mechanisms that has been put forward to explain this phenomenon is negative frequency-dependent selection, which can be caused by different mechanisms. Among these mechanisms is mate choice, or the selection as a potential mate of the rare or dissimilar colour morph by the choosy sex of a given species. In the context of colour polymorphism, mate choice predicts the occurrence of a negative assortative mating pattern, whereby different colour morphs mate more often than expected by chance alone. However, negative assortative mating can also result from other mechanisms, making it, at best, a fallible indicator of a mate choice-driven negative frequency-dependent selection. For this reason, experimental evidence explicitly connecting such a mating pattern to mate choice is necessary to claim that a particular colour polymorphism is being maintained by negative frequency-dependent selection. Here we present experimental evidence backing this relationship for the colour polymorphic marine gastropod Littorina saxatilis from the Ría de Vigo (NW Iberian Peninsula), although how specifically these organisms choose their mates remains unclear. This calls for further experimental efforts to clarify this issue and its relationship to the maintenance of colour polymorphism in L. saxatilis.